Una estrategia para el Estado Contemporáneo: la nueva gerencia pública - Romero-Pérez, Jorge Enrique (2014)
Contemporary public administration has incorporated the language and the perspective characteristic of the private sector, within the broader context of neoliberalism and globalization.